Mechanical behavior of an electrostatically actuated micropump - Faris, Waleed Fekry; Abdel-Rahman, Eihab M.; Nayfeh, Ali H. (2002)
We present a model of an electrostatically actuated micropump employing an annular actuating member. The boundary-value problem describing the static deflection of the plate under the electrostatic force is solved numerically. The eigenvalue problem describing the vibration of the plate around the equilibrium position is also solved numerically for the natural frequencies and mode shapes. The results generated by our model are in good qualitative agreement with reported results for the free vibration of straight annular plates. Moreover, the relation between the maximum deflection and the intensity of the electrostatic potential is in qualitative agreement with the experimental results for micropumps with a square actuating member. The model predicts the deflection accurately for any voltage up to the pull-in voltage.